The Construction and Contents of the Beatty-Michigan Pauline Epistles Codex (⁴⁶). - Nongbri, Brent (Novum Testamentum, 2022)
The surviving portion of the papyrus codex of the letters of Paul split between the Chester Beatty Library and the University of Michigan (⁴⁶) consists of a well preserved but damaged single quire containing parts of nine of Paul's letters. Because the pages of the codex are numbered, scholars have believed that it is possible to reconstruct the original size of the quire, which turns out to be too small for the traditional Pauline corpus of fourteen letters. Many scholars have taken this to mean that the codex did not contain the Pastoral letters (1–2 Timothy and Titus). Jeremy Duff has argued that the copyist increased the number of letters per page in the second half of the codex and intended to add extra leaves in order to produce a codex with all of the fourteen letters found in the majority of undamaged Greek manuscripts of Paul's letters. While Duff's hypothesis has been critically engaged on other grounds, this article assesses Duff's proposed ancient comparanda for the addition of extra folia to the end of a single-quire codex and revisits the problem of the contents of this codex in light of the construction techniques of better preserved single-quire codices.